Life, Love, Lies - Fonkeng, E. F. (Book collections on Project MUSE., 2015)
Life, Love, Lies is a collection of reflections on perhaps the two most mundane yet fundamental aspects of human existence: love and the concept of living. In between, are matters benign and not so benign - on life - amassed, experienced and/or lived, for well over half a century now; on everything from the tabula rasa of childhood to the flow of world history.